Efficacy and Tolerability of Quinacrine Monotherapy and Albendazole Plus Chloroquine Combination Therapy in Nitroimidazole-Refractory Giardiasis: A TropNet Study. (11th June 2021) - Neumayr, Andreas; Schunk, Mirjam; Theunissen, Caroline; Van Esbroeck, Marjan; Mechain, Matthieu; Hatz, Christoph; Mørch, Kristine; Soriano Pérez, Manuel Jesús; Sydow, Véronique; Sothmann, Peter; Kuenzli, Esther; Rothe, Camilla; et al.
Abstract: Background: Giardiasis failing nitroimidazole first-line treatment is an emerging problem in returning European travelers. We present data on the efficacy and tolerability of 2 second-line treatment regimens. Methods: This prospective, open-label, multicenter study assessed the efficacy and tolerability of quinacrine monotherapy (100 mg 3 times per day for 5 days) and albendazole plus chloroquine combination therapy (400 mg twice daily plus 155 mg twice daily for 5 days) in nitroimidazole-refractory giardiasis. The defined end points were the clinical outcome, assessed at week 5 after treatment and the parasitological outcome, assessed using microscopy of 2 stool samples, ≥2 to ≤5 weeks after treatment. Results: A total of 106 patients were included in the study. Quinacrine achieved clinical and parasitological cure in 81% (59/73) and 100% (56/56), respectively. Albendazole plus chloroquine achieved clinical and parasitological cure in 36% (12/33) and 48% (12/25), respectively. All patients (9/9) who clinically and parasitologically failed albendazole plus chloroquine treatment and opted for retreatment with quinacrine achieved clinical cure. Mild to moderate treatment-related adverse events were reported by 45% and 30% of patients treated with quinacrine and albendazole plus chloroquine, respectively. One patient treated with quinacrine developed severe neuropsychiatric side effects. The majority of nitroimidazole-refractory Giardia infections (57%) were acquired in India. Conclusions: Quinacrine was a highly effective treatment in nitroimidazole-refractory giardiasis, but patients should be cautioned on the low risk of severe neuropsychiatric adverse event. Albendazole plus chloroquine had a low cure rate in nitroimidazole-refractory giardiasis. Nitroimidazole-refractory giardiasis was primarily seen in travelers returning from India. Abstract : Giardia duodenalis infections failing nitroimidazole first-line treatment are an emerging problem in travelers returning from tropical and subtropical regions. We present data on the efficacy and tolerability of 2 second-line treatment regimens, quinacrine monotherapy and chloroquine plus albendazole combination therapy.